Pengaruh Entrepreneur Style terhadap Pengembangan Produk UMKM di Desa Karangrejo Kabupaten Malang - Lestari, RR. Hesti Setodyah; Husna Romadhon, Moch Hadi; Rosyadi Hamid , Imron (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2023)
This research aims to determine the influence of socialpreneurship and technopreneurship simultaneously on product development, to determine the influence of socialpreneurship on product development, and to determine the influence of technopreneurship on product development for MSMEs in Karangrejo village, Malang Regency. The research method is quantitative research using a questionnaire. The respondents of this research are MSME entrepreneurs in Karangrejo Village, Malang Regency. Data mining was carried out using data collection techniques using a Likert scale, with 80 respondents from a total population of 100 people. Based on the analysis carried out, the first conclusion is obtained, there is a significant influence of socialpreneurship and technopreneurship simultaneously on product development; secondly, there is a significant influence of socialpreneurs on product development; thirdly, there is a significant influence of technopreneurship on product development